2015
DOI: 10.5539/gjhs.v8n3p193
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Nurses about Standard Precautions for Hospital-Acquired Infection in Teaching Hospitals Affiliated to Zabol University of Medical Sciences (2014)

Abstract: Background and Objectives:Hospital-acquired infection (HAI) is one of the common problems and difficulties faced by hospitals in all countries around the world. Since nurses are part of the healthcare team that plays a unique role in the control of hospital infection, this study is conducted to analyze the knowledge and practice of healthcare personnel about standard precautions for hospital infection.Materials and Methods:This descriptive study was conducted on 170 nurses worked in medical surgical wards, ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
58
16
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 18 publications
16
58
16
6
Order By: Relevance
“…This finding is supported studies from China (27) and other similar studies (19,20). In addition, this study indicated that positive attitude towards infection prevention practices is the core to achieve good infection prevention practices in healthcare facilities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is supported studies from China (27) and other similar studies (19,20). In addition, this study indicated that positive attitude towards infection prevention practices is the core to achieve good infection prevention practices in healthcare facilities.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is much higher than study finding in North West Ethiopia (55.6%) (17), Eastern Ethiopia (53.1%) (25) and finding from Iran (33%) (20). These differences might be due to differences in the experience of HCWs and training exposure.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Therefore, they are more exposed to various NIs [10]. Hence, nurses play a vital role in transmitting NIs, and their compliance with infection control measures seems to be necessary for preventing and controlling NIs [11]. Accordingly, they should be aware of how to prevent transmission of NIs and be knowledgeable of its potential risk to patients, other staff, and as visitors.…”
Section: Introductionmentioning
confidence: 99%
“…Another finding from this study show that subjects who excel in academic have better self-efficacy (Sarani, Balouchi, Masinaeinezhad, & Ebrahimitabs, 2014;Rosen, Zucker, Brody, Engelhard, & Manor, 2009;Scott, Lawson, & Curtis, 2007). Good practice has a significant association with self-efficacy in hand washing practice (Sarani, Balouchi , Masinaeinezhad, & Ebrahimitabs , 2014) The study findings show low knowledge score on hand washing (16.7%). Knowledge score on 7 steps of hand washing is 32.1%, wash hands before touching the face (14.3%) and after touching the face (9.5%).…”
Section: Discussionmentioning
confidence: 77%